Microplastics in human feces: a pilot study exploring links with dietary habits - Alice Refosco; Jutta Dierkes; Tanja Kögel; Simon Nitter Dankel; Johnny Laupsa-Borge; Alessio Gomiero; Damaris Benny Daniel (Microplastics and Nanoplastics)
Abstract Microplastic are an emerging environmental contaminant that have raised concerns regarding their potential impact on human health. Ingestion is considered the primary route of human microplastic exposure, with food and beverage contamination being major contributors. This study aimed to evaluate the applicability of an existing microplastic extraction protocol, design for rat feces, on human fecal samples and to assess the occurrence, polymer composition and potential dietary sources of microplastic in individuals from Norway. Participants were selected based on their seafood consumption status, categorized in seafood consumers (n = 9) and non-seafood consumers (n = 9). The extraction protocol involved the matrix digestion in 15% H2O2: 5% HNO3 and 10% KOH. Microplastic particles were then identified by µ-FTIR. Microplastic were detected in 17 out of 18 fecal samples with a total of 132 particles and sizes ranging from 12.5 to 4065 μm. Polypropylene was the most prevalent polymer (72%), followed by polyethylene (44%) and polystyrene (16%). There was no significant association between microplastic abundance and seafood consumption, or with other food groups, such as chocolate and chips. These findings suggest that dietary habits alone may not be the primary determinant of microplastic exposure. Moreover, this study highlights the necessity for harmonized microplastic extraction protocols and broader investigations into regional and individual variations in microplastic exposure.